Pediatric Reference Intervals for Transferrin Saturation in the CALIPER Cohort of Healthy Children and Adolescents - Higgins, Victoria (EJIFCC, 2017)
BACKGROUND: Transferrin saturation reference intervals specific for age and sex have not been previously reported for the pediatric population. The reference values for transferrin saturation have been previously reported to be lower in children compared to adults, caused by a combination of low serum iron and high serum transferrin levels in children, warranting specific reference intervals. Here we use the original iron and transferrin data from the CALIPER cohort to establish age- and sex-specific pediatric reference intervals for transferrin saturation. METHODS: Iron and transferrin concentrations were measured in serum samples from the CALIPER cohort of healthy children and adolescents on the Abbott Architect c8000. Transferrin saturation was subsequently calculated and statistically relevant age- and sex-partitions were determined. After removing outliers, age- and sex-specific reference intervals with corresponding 90% confidence intervals were calculated using CLSI C28-A3 guidelines. RESULTS: Transferrin saturation required 3 separate age partitions, with an additional sex partition for 14-<19 year olds. Transferrin saturation was more variable during the first year of life, evident by a wider reference interval, which subsequently narrowed at one year until adolescence. Upon adolescence, a sex difference was apparent with females having lower percent transferrin saturation than males. CONCLUSIONS: Age- and sex-specific pediatric reference intervals for transferrin saturation were established based on a large cohort of healthy pediatric subjects. Transference studies suggest that these intervals established using Abbott assays are comparable to those on Beckman, Ortho, Roche, and Siemens assays. Individual laboratories should however verify these reference intervals for their individual instrument and local population as per CLSI guidelines.